Islamic Education Based on Sufi-Transformative Learning: A Philosophical Framework for Pedagogical Change in Pesantren - Taufikin Taufikin; Fajar Syarif; Mowafg Abrahem Masuwd (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Islamic Education Based on Sufi-Transformative Learning: A Philosophical Framework for Pedagogical Change in Pesantren (Islamic Boarding Schools)Objective: This study proposes an integrative framework for Sufi-transformative learning in Islamic pesan-tren, combining transformative learning theory with the philosophy of neo-Sufi education to bridge the conceptual gap. Method: This study uses a qualitative multi-case study design, the research was conducted in two Islamic boarding schools in Central Java, recognized for their strong Sufi traditions. Data were collected through in-depth interviews, participant observation and document analysis. Results: The findings reveal significant transformations in pedagogical practices, including the use of digital tools to support moral learning, increased emphasis on spiritual reflection, and the repositioning of teachers as moral exemplars. Conclusion: Transformative Islamic education in pesantren emphasizes metaphysical awareness and ethical formation, and holds the potential to become an innovative model for holistic Islamic education that bridges tradition and modernity. Contribution: This study offers a new philosophical lens and opens avenues for curriculum development, teacher training, and future research in values-based Islamic pedagogy.INDONESIA: Pendidikan Islam berbasis Pembelajaran Sufistik-Transformatif: Kerangka Kerja Filosofis untuk Perubahan Pedagogis di PesantrenTujuan: Syudi ini mengusulkan kerangka kerja integratif untuk pembelajaran transformatif Sufi di pesantren Islam, dengan menggabungkan teori pembelajaran transformatif dengan filsafat pendidikan neo-Sufi untuk menjembatani kesenjangan konseptual. Metode: Desain penelitian menggunakan studi multi-kasus kualitatif, penelitian ini dilakukan di dua pesantren di Jawa Tengah, yang terkenal dengan tradisi sufistiknya yang kuat. Data dikumpulkan melalui wawancara mendalam, observasi partisipan, dan analisis dokumen. Hasil: Temuan menunjukkan adanya transformasi signifikan dalam praktik pedagogis, yang meliputi penggunaan alat digital untuk meningkatkan pembelajaran moral, penekanan yang semakin kuat pada refleksi spiritual, dan reposisi guru sebagai teladan moral. Kesimpulan: Pendidikan Islam transformatif di pesantren menekankan kesadaran metafisik dan pembentukan etika, dan memiliki potensi untuk menjadi model inovatif dalam pendidikan Islam holistik yang menjembatani tradisi dan modernitas. Kontribusi: Studi ini memberikan kontribusi lensa filosofis baru dan membuka jalur baru untuk pengembangan kurikulum, pelatihan guru, dan penelitian di masa depan dalam pedagogi Islam berbasis nilai.